(untitled) (Journal of actual problems of jurisprudence, 2022)
The article broadly analyzes human rights factor in the regulation of relations in the field of information on the basis of the diversity of opinions existing in the legal literature and norms of international law. Today the information network that governs the world also justifies the need to regulate relationships in this area, where human rights are one of the main aspects. Even other problems set by the international community ultimately serve human rights. For example, ensuring international peace and security ultimately leads to human security. In general, as well as in other areas, the special consideration of the human rights factor in the regulation of relationships in the field of information can be justified by a number of factors. The analysis of the peculiarities of the regulation of relationships is a significant problem in each area. Nowadays, the information network that governs the world also justifies the need to regulate relations in this area, where human rights are one of the main aspects. Finally, the article concludes that when analyzing the general characteristics of the interaction between the regulation of relations in the field of information and the human rights factor, it should be proceeded from the close interaction of these concepts: information objects, information relations, legal regulation, human rights. Keywords: information relations, protection of information, information objects, information systems, legal regulation, information law.